Saving and Economic Growth in South Asia: Evidence from Time Series Analysis - Shah, R K (Economic Journal of Nepal, 2015)
This paper is an attempt to assess causal relationship between GDP and savings in five South Asian countries namely Bhutan, India, Pakistan, Nepal, and Sri Lanka for the period 1983-2010, using unit root test, co-integration, Granger Causality, and Vector Error Correction Models. It has found that savings has significantly contributed to economic growth in Nepal and India while in the case of Bhutan and Sri Lanka, economic growth has significantly contributed to savings. In addition, no causal relationship has found between these variables in Pakistan. Economic Journal of Nepal Vol. 34, No. 2, Issue no. 134, 2011